Hand hygiene among nurses in pediatric blood and marrow transplantation setting: a best practice implementation project. Issue 3 (1st September 2022) - Nedelcu, Viorica; Niculiţă, Oana O.; Toporaş, Elena; Zazu, Mariana; Mazilu, Doina C.; Jiménez, Marina Gallego; Grinţescu, loana M.
ABSTRACT: Objectives: The aim of this project was to promote evidence-based best practice regarding hand hygiene among nurses in a pediatric blood and marrow transplantation (BMT) setting. Introduction: Healthcare-associated infections (HAI) represent important complications of healthcare with potentially major impact on patient outcomes. Most HAI are transmitted through the hands of healthcare professionals (HCP) and therefore hand hygiene is the simplest, most effective and proven method for preventing HAI. However, the overall compliance rate of HCP with hand hygiene remains at a very low level. In this case, it is necessary to implement strategies to improve the compliance with hand hygiene of the HCP with the purpose of reducing HAI rates, mortality and costs, all the more so as it is known that patients with BMT have an increased risk of HAI. Methods: This best practice implementation project was based on the JBI methodological approach and included three phases of activity: a baseline audit, implementation of strategies and a follow-up audit. The project was conducted in the pediatric BMT setting of a large university hospital located in Bucharest, Romania, and the sample included 10 nurses and five relatives of pediatric patients from this ward. Results: As a result of the implementation of strategies, improvements were observed across seven audit criteria, given that for two audit criteria out of a total of nine audit criteria compliance was maximum (100%) since the baseline phase. Moreover, the post implementation audit showed a complete compliance (100%) for six audit criteria. However, for the other three audit criteria the compliance in follow-up audit was high: 92, 85 and 80%, respectively. Conclusion: The strategies applied within this evidence implementation project were appropriate, so the project was a success. However, permanent actions are required to sustain changes in practice and improvements made.